Management of Intracranial Pressure Control in Reciprocal Grade 3 Astrocytoma Patient In Dr. Moewardi General Hospital Surakarta: Case Report - Eko Setijanto; Teddy Wijaya (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2021)
Surgery in patients with astrocytoma is performed based on the size of the tumor in the brain and the functional status of the patients. Management of patients with intracranial hypertension can be guided by monitoring intracranial pressure (ICP) perioperatively. A variety of ventricular, intraparenchymal, and subdural equipment can be installed by neurosurgeons to provide ICP measurements.We reported a 50-year-old female patient, with a complaint of having a speech disorder since four years ago. Preoperative physical examination showed GCS E4V5M6, patient's body mass index was 29.29 kg/m2 (obese). Patient’s physical status was assessed with ASA 3. There was no significant abnormality in laboratory examination. MRI Brain contrast examination showed solid cystic lesion in supratentorial left temporal lobe with size 2.3x3.5x4.7cm accompanied by broad perifocal edema in the left frontal, temporal and parietal lobe. The chest X-ray showed cardiomegaly and pneumonia. Electrocardiography showed normal sinus rhythm.Craniotomy in patients with astrocytoma is performed based on the size of the tumor in the brain and the functional status of the patient. Preoperative evaluation for patients undergoing craniotomy should be carried out to determine the presence or absence of intracranial hypertension. In principle, postoperative management in the ICU is to control the respiratory system, optimize the cardiovascular system, and prevent possible complications.Management of intracranial pressure control in reciprocal grade 3 astrocytoma patient should be paid attention to various things and consider the condition of the patients. Preoperative preparations, as well as perioperative and postoperative monitoring, should be carefully observed to prevent complications that will adversely affect patients.